Arousing Patriotic Feelings over Infrastructural and Moral Deficits in Nigeria: An Exposition of Mustaqbal Ilorin Al-Z?hir of Shaykh Y?suf Alikinl? - Musa Adesina; Abdu Raheem; Kamil Adeleke Adeyemi (The Center for Language Development, Mataram State Islamic University., 2021)
Scholars of Islam contribute a lot to the growth and development of their society, of which those from Nigeria are not left out. Prominent among them in Yorubaland, was Shaykh cAbdus-Sal?m Y?suf Alikinl? whose works were in Arabic Language. His views on political mobilization as a form of patriotism was expressed in one of his manuscripts, Mustaqbal Ilorin Al-Z?hir, which is the focus of this study. His submissions were examined using the text analysis method, where he encouraged Nigerians to cultivate the habit of patriotism which would make them feel concerned about the intolerable infrastructural and moral deficits of the country, thereby spurring them on to take steps for improvement in this regard.